Techno-economic viability, environmental impact and development approaches for photovoltaic pumping system in Cagayan Valley Region - Balderama, O.F.
This paper presents R&D results on the viability, environmental impact and development approach on the adoption and commercialization of a solar powered pumping system for domestic and agricultural uses under Cagayan Valley condition.
Keywords: This paper presents R&D results on the viability, environmental impact and development approach on the adoption and commercialization of a solar powered pumping system for domestic and agricultural uses under Cagayan Valley condition. The resource utilized the existing 24-unit photovoltaic installation with a submersible pump. Climatic data was collected from the nearby agrometeorological station jointly operated by PAGASA and Isabela State University. A water level recorder was used to measure drawdown during pumping test and standard electrical multi-meter was likewise used to monitor the amount of current and voltage generated by the PV system. The CROPWAT simulation model was utilize to benchmark existing climate condition in the study area to verify the suitability of PV-pumping system and in estimating crop and irrigation requirements